How Balanced is the Performance Measurement Through the Balanced Score Card - Irala, Lokanandha Reddy; Reddy, Raghunatha; Pratap Reddy, S. (Indian Journal of Finance, 2008)
In the global knowledge economy, creation, sustenance and application of knowledge has become the key differentiator of success. Traditionally effective management of physical and financial management is considered an important source of competitive edge. Today many companies have realized that management of knowledge and the knowledge workers is a key differentiator of competitive strength. An important fall out of this thinking is rapid changes in the way the performance of an organization and its people is measured. There has been growing criticism of financial measures in performance evaluation system and varieties of new measures were floated in the last two decades. Balanced Score Card is an important one among them . Balanced Score Card is a set of measures that gives top managers a fast yet comprehensive view of the business. It pulls together all the important elements of even a company's competitive agenda. Through this, the top management understands the internal trade offs better-whether the value addition in one area is achieved at the cost of another-what we call "Cannibalizing Effect" . Paradoxically the major limitation of the Balanced Score Card is that it promotes multiple objectives of equal weight, which may create decision making in congruencies. Despite the criticism, the Balanced Score Card continues to be an important tool of performance measurement all over the globe barring it's, the difficulty in balancing the different perspectives of an organization. Use of Balanced Score Card as tool of linking strategy with operations and translating vision into actions is yet to be empirically established.